The Secretin/Pituitary Adenylate Cyclase-Activating Polypeptide/ Vasoactive Intestinal Polypeptide Superfamily in the Central Nervous System - Chu, J. Y.S.; Lee, L. T.O.; Siu, F. K.Y.; Chow, B. K.C. (Central Nervous System Agents in Medicinal Chemistry, 2006)
The secretin/PACAP/VIP superfamily contains at least ten brain-gut peptides, including secretin, pituitary adenylate cyclase-activating polypeptide (PACAP), vasoactive intestinal polypeptide (VIP), glucagon, glucagon-like peptide-1 (GLP-1), glucagon like peptide-2 (GLP-2), gastric inhibitory polypeptide (GIP), peptide histidine isoleucine (PHI) or peptide histidine methionine (PHM), and growth hormone-releasing hormone (GHRH). These peptides exhibit a wide tissue distribution in the peripheral systems, indicating their pleiotrophic actions in the body. Meanwhile, their functions in the central nervious system (CNS) have also been consolidated recently. For instance, most of these peptides have shown to serve as neurotransmitters, neuromodulators, neurotrophic factors, and/or neurohormones in the brain, and hence, their potential as novel CNS agents in treating neurological disorders including Autism, Alzheimer's disease, Parkinson's disease and HIV-associated neuronal cell death were recently exploited. In this article, recent progress in research of peptides in this family with particular emphasis on structures, their central functions and potential use in the treatment of neuronal diseases are reviewed.
Keywords: Secretin/VIP/PACAP family peptides